Photocatalytic Degradation of Crystal Violet Dye in Aqueous Solution using ZnFe2O4-Cellulose Nanocomposite Catalyst - Singh, Alka; Singh, N.B.; Tomar, Richa (Asian Journal of Chemistry, 2023)
The major issue in the modern area is the wastewater discharge, particularly the organic pigments from several industries, which creates various pernicious health hazards. As a result, synthesized zinc ferrites and cellulose nanocomposites are effective photocatalysts used for the detoxification of crystal violet dyes. The crystallite-size of synthesized zinc ferrite nanoparticle was confirmed from XRD by using Scherrer equation to be 25.5 nm. The elemental composition of the zinc ferrite-cellulose nanocomposite was clearly shown by the EDS spectrum. Based on the FESEM micrographs, the zinc ferrite-cellulose nanocomposite morphology revealed a smooth surface with microspheres measuring 500 nm in size. The ZnFe2O4-cellulose nanocomposite demonstrated 92% photocatalytic efficiency for the removal of crystal violet dye at pH 6 after 160 min of sunlight irradiation with a catalyst dosage of 50 mg and an initial dye concentration of 10 ppm. The pseudo-second-order kinetic model was found to be consistent for the photocatalytic process. Finally, the newly developed photocatalyst (ZnFe2O4-cellulose nanocomposites) should be considered better for dye decontamination in wastewater.